Exploring the Relationship between Macrofaunal Biodiversity and Ecosystem Functioning in the Deep Sea - Baldrighi, Elisa; Giovannelli, Donato; D'Errico, Giuseppe; Lavaleye, Marc; Manini, Elena (Frontiers in Marine Science, 2017)
The global scale of the biodiversity crisis has stimulated research into the relationship between biodiversity and ecosystem functioning (BEF). Even though the deep sea is the largest biome on Earth, BEF studies in deep-sea benthic ecosystems are scant. Moreover, the small number of recent studies, which mostly focus on meiobenthic nematodes, report conflicting results that range from a very clear positive relationship to none at all. In this BEF study, the deep-sea macrofauna were used as a model to investigate the structural and functional diversity of macrofauna assemblages at three depths (1200, 1900, and 3000 m) in seven open-slope systems from the North-Eastern Atlantic Ocean to the Central-Eastern Mediterranean Sea. The presence and nature of BEF relationships were studied considering two spatial scales, the large and the basin scale, in different environmental settings. Total benthic biomass and macrofaunal predator biomass were used as proxies to assess ecosystem functioning. Ecosystem efficiency was expressed as macrofaunal biomass to biopolymeric carbon content ratio, macrofaunal biomass to prokaryotic biomass ratio, macrofaunal biomass to meiofaunal biomass ratio, and meiofaunal biomass to prokaryotic biomass ratio. On both large and basin spatial scales, some significant relationships between macrofaunal diversity and ecosystem functioning and efficiency were reported. When significant, the nature of BEF relations was positive and exponential or linear supporting the general idea that a higher diversity can enhance ecosystem functioning. Other BEF relationships were explained by the effect of environmental variables. More data from different deep-sea systems are needed, to better elucidate the consequences of biodiversity loss on the ocean floor.